FACE POLITENESS OF MAKASSAR PEOPLE - Qalbis, Nur (IJLECR (International Journal of Language Education and Cultural Review), 2018)
This research explains faculty aspects among Makassar tribe community in South Sulawesi. The objective is to provide an understanding of Makassar facilitation aspect in Gowa district. This study describes the form of expressions related to the concept of face (self-esteem, image) that is loss of face, face thickness, and face search of speech acts in the community. Face has two aspects: positive face and negative face. This research uses qualitative approach, methods with observation, interview, and recording techniques. The results of this study indicate that there is a shift in the concept of Makassar society face that this is influenced by the level of social, education, and gender. Social status here is no longer influential in preserving the concept of the face. This is because there is a shift between the social statue bangsawa no longer care about it, let alone the young. Furthermore, the level of education, that the higher the education then they will maintain the concept of face in interacting with each other in the community. Finally, sex also determines facial or facial salvation in communicating, compared with male women are very maintaining the concept of advance in communicating and interacting in the community.